Intelligent Multi-Sensor Process Condition Monitoring - Hammad, Firas (2007)
A Master of Science Thesis in Mechatronics Submitted by Firas Hammad Entitled, "Intelligent Multi-Sensor Process Condition Monitoring," December 2007. Available are both Soft and Hard Copies of the Thesis.